The Hegemonic Order in the 21st Century - S. Bielen (Сравнительная политика, 2017)
The concept of the hegemonic order in international relations is, on the one hand, related to the state-centric understanding of the international system, and on the other hand, to the challenging of the thesis of its polyarchism. While historic hegemonies never had a monopoly on exclusivity, the U.S. has achieved a clear and significant advantage over other powers. This was due to numerous reasons. The multidimensionality of the U.S. power means that no one else is able to match the U.S.in military, economic, technological, political, or culturalcivilizational and ideological terms. The United States has become the only power that can effectively stabilize or destabilize the existing global order. The biggest source of current concern is, on the one hand, a contestation of U.S. hegemony in the world, and, on the other, its actual decline.